The company men [videorecording (DVD)] - Wells, John, 1956-; Wells, John, 1956-; Wells, John, 1956-; Affleck, Ben, 1972-; Cooper, Chris, 1951-; Jones, Tommy Lee, 1946-; Bello, Maria, 1967- (Anchor Bay Entertainment, 2011)
Bobby Walker is living the proverbial American dream: great job, beautiful family, shiny Porsche in the garage. When corporate downsizing leaves him and co-workers Phil Woodward and Gene McClary jobless, the three men are forced to re-define their lives as men, husbands, and fathers. Bobby soon finds himself enduring enthusiastic life coaching, a job building houses for his brother-in-law that does not play to his executive skill set, and perhaps there is more to life.